The Role of Ethnicity and Religion in Shaping Nigeria's Foreign Policy in the Post Cold War Years - Monguno, B. (University of Ghana, 2004)
The end of the Cold War has brought about a new dimension in international politics, whereby the thinking of state actors and non-state is no longer guided by East-West considerations. Multi-polarity has emerged with a new set of global concerns which are influencing the domestic set up of many nation- states. Most of these concerns have tended to have ethno-religious undertones, consequently inspiring internal reaction. The "domestication" of sensitive international issues very often impacts on the foreign policy decision-making process, especially in a pluralistic society with conflicting interest groups. This has been a common feature in Nigeria's foreign policy since independence. This study examines the influence of ethnicity and religion in shaping Nigeria's foreign policy in the post-Cold War era. The research has revealed that Nigeria's multi-cultural, multi-religious, multi-ethnic characteristic is to a very large extent, influential in her foreign policy process. The numerous crises in Nigeria are predominantly triggered by ethno-religious factors which have equally impacted on Nigeria's relations with state and nonstate actors in the international community. Some contemporary global issues, particularly the war against terrorism have engendered resentment within certain segments of the Nigeria nation. Recommendations are made to reverse the destabilizing role of ethnicity and religion in Nigeria's foreign policy process and improve the existing climate of suspicion and acrimony.
MA. International Affairs
Keywords: Cold War; Ethnicity; Religion; Nigeria; Politics; Independence